Professional Android sensor programming - Milette, Greg; Stroud, Adam (Wrox programmer to programmer, 2012)
Learn to build human-interactive Android apps, starting with device sensors This book shows Android developers how to exploit the rich set of device sensors—locational, physical (temperature, pressure, light, acceleration, etc.), cameras, microphones, and speech recognition—in order to build fully human-interactive Android applications. Whether providing hands-free directions or checking your blood pressure, Professional Android Sensor Programming shows how to turn possibility into reality. The authors provide techniques that bridge the gap between accessing sensors and putting them to meaningful use in real-world situations. They not only show you how to use the sensor related APIs effectively, they also describe how to use supporting Android OS components to build complete systems. Along the way, they provide solutions to problems that commonly occur when using Android's sensors, with tested, real-world examples. Ultimately, this invaluable resource provides in-depth, runnable code examples that you can then adapt for your own applications. * Shows experienced Android developers how to exploit the rich set of Android smartphone sensors to build human-interactive Android apps * Explores Android locational and physical sensors (including temperature, pressure, light, acceleration, etc.), as well as cameras, microphones, and speech recognition * Helps programmers use the Android sensor APIs, use Android OS components to build complete systems, and solve common problems * Includes detailed, functional code that you can adapt and use for your own applications * Shows you how to successfully implement real-world solutions using each class of sensors for determining location, interpreting physical sensors, handling images and audio, and recognizing and acting on speech Learn how to write programs for this fascinating aspect of mobile app development with Professional Android Sensor Programming.